Pharmacokinetic, pharmacodynamic, and immunogenic rationale for optimal dosing of pegvaliase, a PEGylated bacterial enzyme, in adult patients with phenylketonuria. Issue 5 (31st May 2021) - Qi, Yulan; Patel, Gina; Henshaw, Joshua; Gupta, Soumi; Olbertz, Joy; Larimore, Kevin; Harding, Cary O.; Merilainen, Markus; Zori, Roberto; Longo, Nicola; Burton, Barbara K.; Li, Mingjin; et al.
Abstract: Phenylketonuria (PKU), a deficiency in the activity of the enzyme phenylalanine hydroxylase, leads to toxic levels of phenylalanine (Phe) in the blood and brain. Pegvaliase (recombinant Anabaena variabilis phenylalanine ammonia lyase conjugated with polyethylene glycol) is approved to manage PKU in patients aged greater than or equal to 18 years in the United States and in patients aged greater than or equal to 16 years in the European Union. Pharmacokinetic, pharmacodynamic, and immunogenicity results from five open‐label pegvaliase trials were assessed. Studies with induction/titration/maintenance (I/T/M) dosing regimens demonstrated pharmacokinetic stabilization and sustained efficacy associated with maintenance doses (20, 40, or 60 mg/day). Immune‐mediated pegvaliase clearance was high during induction/titration phases when the early immune response was peaking. The combination of low drug dosage and high drug clearance led to low drug exposure and minimal decreases in blood Phe levels during induction/titration. Higher drug exposure and substantial reductions in blood Phe levels were observed later in treatment as drug clearance was reduced due to the maturation of the immune response, which allowed for increased dosing to target levels. The incidence of hypersensitivity reactions was temporally associated with the peaking of the early antidrug immune response and decreased with time as immune response matured after the first 6 months of treatment. These results support an I/T/M dosing regimen and suggest a strategy for administration of other nonhuman biologics to achieve efficacy and improve tolerability.